POLITIK HUKUM PEMBERANTASAN TINDAK PIDANA KORUPSI YANG MERUGIKAN KEUANGAN NEGARA UNTUK MEWUJUDKAN KEMANFAATAN HUKUM SERTA KESEJAHTERAAN MASYARAKAT - Asy’ari, Moh. H. Hasyim (PT. Hafasy Dwi Nawasena, 2023)
Corruption is still a major problem in developing countries. Corruption has become a fundamental problem and is even rooted in the fabric of society in Indonesia, making it difficult to eradicate. Corruption eradication has been attempted through various means but until now corruption still thrives in Indonesia. Corruption in Indonesia is further exacerbated by the times and the human mindset that prioritizes material life. Based on the 2022 year-end report survey conducted by ICW (Indonesian Corruption Watch) shows that the eradication of corruption perception index (IPK) in Indonesia decreased from a score of 38 to a score of 34, making Indonesia ranked 110 out of 180 countries. According to records released by TI Indonesia, Indonesia is currently ranked 1 (one) or 3 (three) of the most corrupt countries in the world and in Southeast Asia lags far behind Singapore, Malaysia, Timor Leste, Vietnam and Thailand. The research method is normative juridical research. The research was conducted by examining theories, concepts and laws and regulations related to the research. Corruption crimes will cause state losses but also a decrease in the quality of public services. This is because the judicial process of corruption has a very large cost allocation in its settlement. The government needs to reform the law governing the crime of Corruption in order to create a more effective and effective legal system.